Through the looking glass: memory, myth and policing the past - Lawther, Cheryl (Policing and society, 2022)
The legacy of the Northern Ireland conflict continues to weigh heavily on the Police Service of Northern Ireland’s institutional memory and contemporary policing practices. In this paper, we argue that the tension between competing interpretations of organisational memory and the need to ‘police’ the past has contributed to a ‘through the looking glass’ phenomenon as regards the policing past and efforts to ‘deal with’ the legacy of the Northern Ireland conflict. The article opens with an examination of the contested memory of policing in Northern Ireland. We then explore how, on the one hand, from a policing perspective, dealing with the past has been regarded as an opportunity to ‘celebrate’ aspects of the policing past but on the other, has reinforced a desire to ‘censure’ the less palatable aspects of police conduct during the conflict. Relatedly, we then interrogate how this desire to ‘secure the past’ has translated into the argument that existing and prospective mechanisms of truth recovery risk ‘re-writing’ the history of the conflict. Finally, the article considers how efforts at truth recovery have been acted upon and received by contemporary policing bodies. This part of the article lays bare both the practical challenges of ‘doing’ truth recovery within a policing framework and the need to ‘secure’ the memory of the policing past. The conclusion argues for the separation of policing and ‘the past’ and the removal of legacy work from policing bodies whose predecessor force was both a victim and perpetrator of that legacy of political violence.